Monetary Union in West Africa : Who Might Gain, Who Might Lose, and Why? - Masson, Paul (IMF Working Papers; Working Paper ;, 2002)
We develop a multicountry model in which governments aim at excessive spending in order to serve the narrow interests of the group in power. This puts pressure on the monetary authorities to extract seigniorage, and thus affects the incentives countries would have to participate in a monetary union. This feature, ignored by the monetary union literature for Europe, is potentially important in Africa. We calibrate the model to data for West Africa and use it to assess proposed ECOWAS monetary unions. We conclude that monetary union with Nigeria would not be in the interests of other ECOWAS countries, unless it were accompanied by effective discipline over Nigeria's fiscal policies.